Анализ энергетических характеристик резонаторной системы для измерения хемилюминесценции семян подсолнуха - Чёрная, Мария Александровна (НТУ "ХПИ", 2014)
Проведен энергетический анализ резонаторной системы для измерения сверхслабого свечения семян подсолнуха.

The paper makes an analysis of a resonator system for measuring superweak luminescence of sunflower seeds.
Analysis of energy characteristics of resonator system for measurement of chemiluminiscense of sunflower seeds
Keywords: частота ЭМП; экономический анализ; ЭМИ; фотоэлектронный умножитель; sunflower seeds; EMF frequency; resonator systems